A dynamic interactive vehicle model for modelling traffic beyond the microscopic level. (10th August 2009) - Henclewood, Dwayne; Ni, Daiheng
Recent developments of inter-vehicular wireless communication technologies have motivated many innovative applications aiming at significantly increasing traffic throughput and improving highway safety. Powerful traffic simulation is an indispensable tool for developing these applications and studying their effects before large-scale deployment. One of the necessary advances to such a tool is to incorporate vehicle dynamics in traffic simulation so that the effects of improved driving strategies and cooperation between drivers can be examined at a great level of detail. Existing dynamic vehicle models, owing to their complexity for high modelling fidelity, are not suited for efficient traffic simulation involving many vehicles. To fill the gap, we propose a simple Dynamic Interactive Vehicle (DIV) model that requires little calibration effort and fewer computational resources. The DIV model takes as input a driver's desired acceleration, deceleration and steering, and outputs vehicle dynamic responses, including longitudinal and lateral accelerations and yaw velocity.